Strengthening Millennial Teachers Commitment to Become Edupreneurs - Hadi, Tan; Sihombing, Sabrina Oktaria; Tukiran, Martinus; Wijaya, Rizky Charles (Aptisi Transactions On Technopreneurship (ATT), 2024)
Committed millennial teachers are highly dedicated and engaged in their profession. They aim to deliver high-quality educational services and continuously evolve as edupreneurs. Renowned for their creativity and innovation, they generate fresh ideas for educational ventures. This study examines the impact of Supervisory Support (SS) and the level of spirituality in the workplace (WS) on the Organizational Commitment (OC) of millennial teachers in Indonesia, with Job Embeddedness (JE) and Well-being (WB) as mediator variables. The research methodology employed is quantitative, utilizing Structural Equation Modeling (SEM). A total of 302 questionnaires were distributed to millennial teachers working in private schools. The results indicate that JE significantly mediates the relationship between principal support and OC. However, WB is a significant mediator between the level of spirituality at work and OC. Moreover, while supervisor support did not significantly impact OC, the level of workplace spirituality demonstrated a significant influence on the organizational commitment of millennial teachers. These findings provide novel insights into the factors influencing the retention of millennial teachers, aiding in the development of human resource management strategies in the education sector.